Optimalisasi Peran Masjid Sebagai Sarana Ibadah Dan Pendidikan Islam (Studi Kasus Di Masjid Namira Lamongan) - Septiana Purwaningrum (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2021)
This study aims at describing the strategy Islamic worship and Islamic education services which carried out by the administrators of Namira Mosque. In this paper, there are three issues that are discussed, those are mosque management, optimalization of the role of mosque administrators, and inhibiting factors and supporting the implementation of the programs that being carried out. This study is qualitative research which used a case study. The data collection techniques used are observation, interview, and documentation. The data validity testing that used are triangulation of the methods and data sources. The results revealed from this study are: first, Namira mosque carries out of the mosque management function which includes planning, organizing, actuating and controlling, and has been running well; second, the optimalizatzion of the role of the administrators of Namira mosque is to provide the best service to the worshippers by diversifying their activities and providing an adequate infrastucture; third, the supporting factors of optimalization of the role and mosque function are good and adequate mosque facilities, funding supported from the owner institution, totality and loyalty of the mosque administrators. The inhibiting factor can be said to be almost non-existent, only motivation of the worshippers that are not being consitent yet because of their own bussiness.